Turbulent Flow Analysis with Banach and Sobolev Spaces in the LES Method Incorporating the Smagorinsky Subgrid-Scale Model - Rômulo Damasclin Chaves dos Santos; Jorge Henrique Oliveira Sales (The Journal of Engineering and Exact Sciences)
The mathematical analysis, applied in this work, serves as a pillar for a broader investigation on the regularity of the Navier-Stokes Equations. In this context, this investigation marks a significant step forward in the advancement of the Smagorinsky model coupled with the LES methodology, resulting, based on the Banach and Sobolev Spaces, a new theorem that points the way to the construction of an anisotropic viscosity model (not yet discussed in the present work). At first, the effort dedicated here aims to present a more comprehensive mathematical analysis, promoting a more leveled understanding of the challenge posed by the regularity of the Navier-Stokes equations.